Sugarcane residue management impact soil greenhouse gas - Rose Luiza Moraes Tavares; Kurt Spokas; Kate Hall; Edward Colosky; Zigomar Menezes de Souza; Newton La Scala (Ciência e Agrotecnologia)
ABSTRACT Mechanized sugarcane harvest is replacing the historic practice of field burning, due to environmental concerns of the particulate and emissions during burning. However, the impact of these practices on soil greenhouse gas (GHG) production potential is not fully known. Thus, the present work quantified the potential production, in 1 g of soil, of greenhouse gases (GHG) in three systems of sugarcane management. The systems were: area with a history of burning sugarcane before harvest (B) and another with two systems of management of “green sugarcane” in two periods of implantation - 5 (G-5) and 10 years (G-10). A laboratory incubation experiment was used to assess the production potentials of carbon dioxide (CO2), nitrous oxide (N2O) and methane (CH4) in 1g of soil samples by the different sugarcane management systems. The results of this study demonstrate that the sugarcane management systems had an impact on the potential production of CO2 in the soil. In addition, when the results of gases were divided from convex and concave areas, differences in CO2 patterns between areas B and G-10 were observed, with greater emission in the G-10 area, probably due the residue on the soil surface.